2014
DOI: 10.2214/ajr.13.11409
|View full text |Cite
|
Sign up to set email alerts
|

Low-Normal Lung Volume Correlates With Pulmonary Hypertension in Fibrotic Idiopathic Interstitial Pneumonia: Computer-Aided 3D Quantitative Analysis of Chest CT

Abstract: The relative CT volume of any single lesion was of limited value in predicting pulmonary hypertension in patients with pulmonary fibrosis and emphysema. In these patients, normal(%), measured by a 3D computer-aided system, was correlated with pulmonary hypertension measured by RHC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
0
13
0
2
Order By: Relevance
“…PVV was also found to be a more malignant prognostic determinant in patients with increased fibrosis on CT. Regarding the visual CT variables that were independently predictive of mortality, traction bronchiectasis severity [23e26] and the pulmonary artery diameter [27,28] have both been previously shown to strongly predict outcome across various fibrosing lung diseases, but were not examined in previous studies investigating uILD [4,29].…”
Section: Discussionmentioning
confidence: 99%
“…PVV was also found to be a more malignant prognostic determinant in patients with increased fibrosis on CT. Regarding the visual CT variables that were independently predictive of mortality, traction bronchiectasis severity [23e26] and the pulmonary artery diameter [27,28] have both been previously shown to strongly predict outcome across various fibrosing lung diseases, but were not examined in previous studies investigating uILD [4,29].…”
Section: Discussionmentioning
confidence: 99%
“…Disagreements between the two radiologists after the first assessment were resolved by discussion. We also used computer-aided 3D quantitative analysis of chest HRCT to automatically categorize the lungs in the 3D CT images pixel-by-pixel with Gaussian histogram-normalized relations, and relative volume of disease extent (%) to HRCT lung volume was calculated [26, 27]. A previous study reported that an easily applicable, limited/extensive disease staging system for SSc-ILD based on combined evaluation with HRCT and pulmonary function testing (PFT) provides discriminatory prognostic information [28].…”
Section: Methodsmentioning
confidence: 99%
“…Disease extent (%) on HRCT was calculated by a three-dimensional computeraided system (i.e., Gaussian histogram normalized correlation) of CT images (24,25). Pathological analysis was classified according to the current classification of idiopathic interstitial pneumonias by two pulmonary pathologists (T.T.…”
Section: Study Samplementioning
confidence: 99%